Environmental sensitivity and knowledge base of grade school teachers in environmental education implication to teacher training - De Guzman, Sarah A. (2005)
The study was designed to provide a research base for teacher training institutions by assessing the environmental sensitivity and knowledge base in environmental education (EE) of grade school teachers. The sample consisted of 75 grade school teachers in the CAMANAVA area. The following phases were followed: pilot test of the "Environmental Sensitivity Instrument Teachers Version"; seminar-workshop where teachers were asked to fill out servey forms and information sheets; and identification of the gaps in environmental knowledge of the teachers. Results showed that the environmental sensitivity level of the teacher-respondents is very high although they have limited knowledge base on EE. Because of these, they are unlikely to produce environmentally literate students but can pave the way in shaping students' environmental behavior
Thesis (M.A. Environmental Education)--University of the Philippines, Diliman.
Keywords: Elementary school teachers -- Philippines -- Manila Metropolitan Area -- Training of; Environmental education -- Philippines -- Manila Metropolitan Area